The bitter season [large type] - Hoag, Tami (Kovac and Liska., 2016)
"As the dreary, bitter weather of late fall descends on Minneapolis, Detective Nikki Liska is restless, already bored with her new assignment to the cold case squad. She misses the rush of pulling an all-nighter and the sense of urgency of hunting a desperate killer on the loose. Most of all she misses her old partner, Sam Kovac. Kovac is having an even harder time adjusting to Liska's absence, saddled with a green new partner younger than most of Sam's wardrobe. But Kovac is distracted from his troubles by an especially brutal double homicide: a prominent university professor and his wife, bludgeoned and hacked to death in their home with a ceremonial Japanese samurai sword. Liska's case--the unsolved murder of a decorated sex crimes detective--is less of a distraction: Twenty five years later, there is little hope for finding the killer who got away. Meanwhile, Minneapolis resident Evi Burke has a life she only dreamed of as a kid in and out of foster homes: a beautiful home, a family, people who love her, a fulfilling job. But a danger from her past is stalking her idyllic present. A danger bent on destroying the perfect life she was never meant to have. As the trails of two crimes a quarter of century apart twist and cross, Kovac and Liska race to find answers before a killer strikes again." --